Vitamin D deficiency reduces the benefits of progesterone treatment after brain injury in aged rats - Cekic, Milos; Cutler, Sarah M.; VanLandingham, Jacob W.; Stein, Donald G. (Neurobiology of aging, 2011)
Administration of the neurosteroid progesterone (PROG) has been shown to be beneficial in a number of brain injury models and in two recent clinical trials. Given widespread vitamin D deficiency and increasing traumatic brain injuries (TBIs) in the elderly, we investigated the interaction of vitamin D deficiency and PROG with cortical contusion injury in aged rats. Vitamin D deficient (VitD-deficient) animals showed elevated inflammatory proteins (TNFα, IL-1β, IL-6, NFκB p65) in the brain even without injury. VitD-deficient rats with TBI, whether given PROG or vehicle, showed increased inflammation and greater open-field behavioral deficits compared to VitD-normal animals. Although PROG was beneficial in injured VitD-normal animals, in VitD-deficient subjects neurosteroid treatment conferred no improvement over vehicle. A supplemental dose of 1,25-dihydroxyvitamin D 3 (VDH) given with the first PROG treatment dramatically improved results in VitD-deficient rats, but treatment with VDH alone did not. Our results suggest that VitD-deficiency can increase baseline brain inflammation, exacerbate the effects of TBI, and attenuate the benefits of PROG treatment; these effects may be reversed if the deficiency is corrected.